HIV Patient with Mucous Membrane Pemphigoid: A Case Report - Singh, AP; Chaitra, TR; Ravishankar, TL; Singh, SP; Mohapatra, AK (Ethiopian journal of health sciences, 2014)
Mucous Membrane Pemphigoid, a new denomination of cicatricial pemphigoid, encompasses a group of chronic subepithelial autoimmune blistering diseases that predominantly affect the oral cavity and the eyes (conjunctivitis and symblepharon). A rare case of Mucous Membrane Pemphigoid (MMP) in a human immunodeficiency virus (HIV) positive patient is discussed with clinicohistopathological presentation. Since our patient was HIV-positive and had lesions restricted to the oral mucosa with ocular involvement, only topical and intralesional steroids were preferred as the first line of treatment. Systemic corticosteroid therapy raises a concern regarding immunosuppression.